2014
DOI: 10.3109/00365513.2014.984319
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum levels of calprotectin (MRP8/MRP14) in patients with Behçet's disease and its association with disease activity and quality of life

Abstract: Calprotectin may play a significant role in the pathogenetic mechanisms of BD. Further insight into this area of research might provide opportunities to develop novel treatment strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 46 publications
1
13
1
2
Order By: Relevance
“…In a study in which serum calprotectin level was analyzed in BD, calprotectin serum levels were found to be significantly higher in cases with BD compared to healthy controls; however serum calprotectin levels demonstrated no correlation with BD activity in that study [6]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study in which serum calprotectin level was analyzed in BD, calprotectin serum levels were found to be significantly higher in cases with BD compared to healthy controls; however serum calprotectin levels demonstrated no correlation with BD activity in that study [6]. …”
Section: Discussionmentioning
confidence: 99%
“…FC becomes evident during cell activation or death. We encountered a very low number of studies investigating the level of FC in BD in the literature review we performed [6]. The aim of this study was to investigate the role of FC in the evaluation of intestinal involvement in BD.…”
Section: Introductionmentioning
confidence: 99%
“…152 CLP was also tested as a disease biomarker, but no correlations were found with disease activity scores or quality of life indices in BD patients. 152 Uveitis and oral aphthous ulcerations might be potential sources of S100A8 and S100A9 production in BD.…”
Section: Behç Et's Diseasementioning
confidence: 99%
“…152 CLP was also tested as a disease biomarker, but no correlations were found with disease activity scores or quality of life indices in BD patients. 152 Uveitis and oral aphthous ulcerations might be potential sources of S100A8 and S100A9 production in BD. In fact, raised CLP serum levels have been found in patients with uveitis [153][154][155] and it has been shown that mucosal squamous epithelial cells can express CLP under inflammatory conditions.…”
Section: Behç Et's Diseasementioning
confidence: 99%
“…Calprotectin (MRP8/MRP14) is expressed by activated phagocytes, granulocytes, monocytes, and vascular endothelial cells; is recognized by tolllike receptors; and induces a thrombogenic and inflammatory response in human microvascular endothelial cells. Serum levels of calprotectin were significantly higher in patients with Behçet's disease compared with healthy controls [23]. Ischaemia-modified albumin (IMA) is a sensitive biomarker of ischaemia and oxidative stress.…”
Section: The Relation Between Vascular Involvement and Endothelial Dymentioning
confidence: 99%